Development of Arduino-Based Temperature Control Teaching Aids with Matlab Interface as a Tool for Newton Cooling Practicum - Anggereni, Santih; Tamsil; Irwan, Anas; Kusmiran, Amirin; Qaddafi, Muhammad; Umar Dani, Ali (Jurnal Pendidikan Fisika, 2026)
Physics practicums require accurate, efficient, and traceable measurement systems, particularly in thermodynamic experiments involving continuous temperature changes. In the Newtonian Cooling practicum, conventional measurements with thermometers and stopwatches often lead to recording errors, inaccurate synchronization of temperature and time, limited data density, and reduced student focus on physical interpretation. This study aimed to develop, validate, and assess the practicality of an Arduino-based temperature control teaching aid integrated with a MATLAB graphical user interface (GUI) to support real-time data acquisition in the Newtonian Cooling practicum. The research employed a Research and Development (R&D) approach using the 4D model, consisting of the Define, Design, Develop, and Disseminate stages, with product development limited to expert validation and minimal practical testing. The tool was developed using an Arduino Uno microcontroller, a DS18B20 temperature sensor, and a MATLAB GUI that displays temperature-time graphs and automatically stores measurement data in Excel. The study involved two expert validators and 10 Physics Education students who participated in the Thermodynamics practicum. The validation results showed that all assessed indicators, including tool recognition, user control, application display, application assistance, and application output, obtained the highest score of 4, indicating very high validity. The practicality assessment also showed excellent results, with an average score of 4.0 and 98% of students reporting positive responses, indicating that the tool was highly practical for practicum use. The novelty of this study lies in integrating real-time temperature measurement, automatic temperature-time data synchronization, graphical visualization, and direct data storage into a single practicum-oriented system. The findings indicate that the developed teaching aid improves the efficiency and accuracy of temperature measurement, reduces manual recording errors, and helps students focus on analyzing cooling phenomena. This study contributes to physics education by providing an affordable, valid, and practical microcontroller-based teaching aid that strengthens laboratory-based learning and promotes data-driven scientific reasoning.